Correlation Between The Knowledge On Health Effects Of Smoking And Motivation On Smoking Cessation In Ex-Smokers Of Lung Department Patients, Siloam General Hospital, Lippo Village. - Wong, Clarinda; Lucas, Brian; Sungono, Veli; Kurniawan, Andree; Widysanto, Allen (Medicinus, 2020)
Introduction: Data from WHO showed that deaths caused by tobacco reaches approximately ± 6 million deaths annually. There are many information about the danger of smoking which spreading from various sources. The level of  knowledge about the danger of smoking can be associated with motivation to stop smoking. Therefore, motivation toward smoking cessation arises if someone knows the benefits that can be taken, through an adequate knowledge.Aim: To determine the relationship between the level of knowledge on the health effects of  smoking with motivation to stop smoking in ex-smokers of lung department patients at Siloam General Hospital, Lippo Village.Methodology: This is a cross-sectional study, analyzing 138 ex-smokers of Siloam General Hospital’s lung department patients using consecutive sampling techniques.Results: the results showed 73.2% of people have good knowledge about the danger of smoking and 26.8% are not. Then, 58% of people have high motivation to stop smoking and 42% have low motivation. The results of statistical test using Chi Square showed a significant relationship between the level of knowledge and the motivation to quit smoking (OR = 4.293 [95% CI: 1,921-9,594], P<.001). The results of the multivariate logistic regression test showed educational factors (P=0.014), and the frequency of smoking (P=0.007) also influence the motivation to stop smoking.Conclusion : There’s a significant relation between knowledge about the danger of smoking and the motivation to quit smoking.